Articulation between argumentation and conceptual, epistemic and social practices in the Science classroom (Research, Society and Development, 2019)
The purpose of this essay is to discuss the possibility of articulation between the argumentation, in the perspective of the Toulmin’s pattern, and the development of conceptual, epistemic and social practices in the teaching of Science, from national and international scientific research. To achieve such an intention, it’s carried out an investigation of qualitative approach, in which we developed a bibliographical research in books and scientific articles related to the theme, considering the contribution of diverse authors. The studies show the relevance of the articulation of the argumentative process and the conceptual, epistemic and social practices during the construction of scientific knowledge, highlighting the need for an enabling environment for such harmonization to take place. Besides that, the argumentative actions depend on the work of the educator as epistemic and social authority that promotes the development of the debates and defenses of ideas for the deepening of the understanding of the topics covered. It’s concluded that the harmonization between the structurally valid arguments and the different conceptual, epistemic and social practices is perceived as constituting the construction of a way of looking, giving meaning to phenomena and legitimizing the knowledge produced in the perspective of school Science.